Pengaruh Pertumbuhan Ekonomi Dan Inflasi Terhadap Tingkat Pengangguran Di Sumatera Barat - Gina Permata Sari; Tartila Devy (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The purpose of this research is to determine the effect of economic growth and inflation on the unemployment rate in West Sumatra. This research is quantitative research with secondary data from the 1992-2021 observation period. In this research, the technique of data collection is the documentation method. This method is carried out using documents or research supporting data, such as data on economic growth, inflation and unemployment rates, taken from the official BPS website. The collected data were analyzed using multiple linear regression analysis with the help of SPSS 25. The research results prove that economic growth and inflation partially have no significant effect on the unemployment rate in West Sumatra between 1992 and 2021. The significance value of the economic growth variable is 0.824 greater than 0.05 and the inflation variable is 0.987 > 0.05. That is, if economic growth and inflation increase, the unemployment rate will also increase. Meanwhile, simultaneous economic growth and inflation had no effect on the unemployment rate in W Sumatra from 1992 to 2021 with a significance level of 0.960 greater than 0.05. The R2 value is 0.003, which means that the ability of the independent variables (economic growth and inflation) to explain the dependent variable (unemployment rate) is 3%. More than 97% is explained by other variables not reviewed in this research.